Design, synthesis and evaluation of antiestrogen and histone deacetylase inhibitor molecular hybrids. Issue 24 (15th December 2015) - Mendoza-Sanchez, Rodrigo; Cotnoir-White, David; Kulpa, Justyna; Jutras, Isabel; Pottel, Joshua; Moitessier, Nicolas; Mader, Sylvie; Gleason, James L.
Graphical abstract: Abstract: The combination of antiestrogens and histone deacetylase inhibitors (HDACi) has been found to be antiproliferative in breast cancer models. We designed and synthesized hybrid structures which combined structural features of the pure antiestrogen ICI-164, 384 and HDACi's SAHA and entinostat in a single bifunctional molecule. The hybrids retained antiestrogenic and HDACi activity and, in the case of benzamide hybrids, were selective for Class I HDAC3 over Class II HDAC6. The hybrids possessed low micromolar to high nanomolar activity against both ER+ MCF-7 and ER− MDA-MB-231 breast cancer cell models.